Morality in the arrangement of Regional Budget as an Effort to Reduce Flypaper Effect: a Critical Habermasian Perspective - Nursal Ikhsan; Bertha Beloan; Muhammad Husni; Frischa Faradilla Arwinda Mongan (International Journal of Religious and Cultural Studies, 2023)
A condition where there is a difference in the decision to spend money earned for free and money raised privately is a flypaper effect. The aim of the research was to map morality level of Regional Head, Regional Government Budget Team, the members of Regional Parliament, and Regional Apparatus Work Unit in the arrangement process of Regional Budget in the Regency of Selayar Islands. The research used critical paradigm, especially Habermas critical theory starting from social evolution based on the theory of Kohlberg’s morality consciousness development. The result of the research indicate that the moralty level of executive and legislative members is still in the first two steps of preconventional level as the reflection of public space morality. Preconventional morality level explains that the dominant opportunistic behavior of executive and legislative members in Regional Budget is a symptom and evidence of waning, limited access, exclusivity, hegemony, and disintegration of public space. The role of flypaper effect is a picture of fiscal decentralization system which even burdens communication process in lifeword named local government. Another finding reveals that patron-client theory has accompanied agency theory in forming executive legislative interaction. Habermas proposes publicity principles and communicative action to improve morality consciousness development level that leads to communication in lifeword without domination